Risk of cardiovascular toxicity with combination of immune-checkpoint inhibitors and angiogenesis inhibitors: a meta-analysis - Inno, Alessandro; Veccia, Antonello; Madonia, Giorgio; Berti, Alvise; Bortolotti, Roberto; Incorvaia, Lorena; Russo, Antonio; Caffo, Orazio; Gori, Stefania (Frontiers in Cardiovascular Medicine, 2024)
Background: Combinations of immune checkpoint inhibitors (ICIs) and angiogenesis inhibitors (AIs) have been investigated for the treatment of several tumor types. Both ICIs and AIs may lead to cardiovascular adverse events, and their combination may potentially increase the risk for cardiovascular toxicity.Objectives: In the present meta-analysis, we aim to assess the cardiovascular toxicity of ICIs plus AIs versus AIs alone. Secondary objectives are non-cardiovascular adverse events and efficacy.Methods: Systematic review was performed according to PRISMA statement. Phase II and III randomized clinical trials were identified by searching the MEDLINE/PubMed, Cochrane Library and ASCO Meeting abstracts, from inception to June 2022. The pooled risks for overall response rate (ORR), 1-year progression-free survival (PFS), adverse events (AEs), immune-related AEs, (irAEs), hypertension, and vascular events defined as stroke, myocardial infarction and pulmonary embolisms, were calculated.In terms of cardiovascular toxicity, we found higher risk for severe hypertension among patients treated with ICIs plus AIs as compared with those receiving AIs (OR 1.24, 95%CI 1.01-1.53), but no significant difference was found for any-grade hypertension, and for vascular events. There was also no difference in terms of overall AEs, whereas the incidence of irAEs was increased in the ICIs plus AIs arm, as expected. In terms of efficacy, ICIs plus AIs achieved better ORR (OR 2.25, 95%CI 1.70-2.97) and PFS (HR 0.49, 95%CI 0.39-0.63) as compared to AIs alone.The addition of ICIs to AIs significantly increased the risk of high-grade hypertension, but not that of acute vascular events.